Transvenous extraction of advisory implantable cardioverter defibrillator leads with a relatively long implant duration. Issue 4 (October 2018) - Goya, Masahiko; Nagashima, Michio; Hiroshima, Ken-ichi; Hayashi, Kentaro; Makihara, Yu; Fukunaga, Masato; An, Yoshimori; Ohe, Masatsugu; Sasaki, Takeshi; Shiohira, Shinya; Shirai, Yasuhiro; Kawabata, Mihoko; et al.
Highlights: All 28 advisory implantable cardioverter-defibrillator (ICD) leads were removed successfully. Transvenous lead extraction of advisory ICD leads with long implant duration is safe. Transvenous lead extraction of advisory ICD leads is useful in Japanese patients. Abstract: Background: Optimal management of advisory implantable cardioverter defibrillator (ICD) leads has not been established. Several studies were reported concerning the lead extraction of advisory ICD leads, but the implant duration of those studies was short. We estimated the efficacy of lead extractions of advisory ICD leads with a relatively longer duration in Japanese patients. Methods: We retrospectively analyzed 28 patients who underwent a lead extraction at Kokura Memorial Hospital and Tokyo Medical and Dental University Hospital [Fidelis (Medtronic, Minneapolis, MN, USA): n  = 19, Riata (St. Jude Medical, Sylmar, CA, USA): n  = 8, Isoline (SORIN CRM SAS, Clamart, France): n  = 1]. The mean implant duration was 63.3 ± 19.3 months. The indications were device related infections in 3, electrical lead failures in 18, electrical lead failures and venous obstructions in 3, and prophylactic reasons in 4 patients. Inappropriate shocks because of electrical lead failures were observed in 9 patients. Results: Complete removals were achieved of all 28 advisory leads. In 23 out of 28 patients, new ICD leads were implanted during the same procedure. In one patient, open chest surgery was performed for a hemothorax that occurred during a new ICD lead implantation just after successfully removing the advisory ICD lead. There were no other major or minor complications. Conclusion: Transvenous extractions of advisory ICD leads with relatively long implant duration were performed with a high success rate and low complication and mortality rate in Japanese patients.